Corporate R&D and Stock Returns: International Evidence. (8th June 2022) - Hou, Kewei; Hsu, Po-Hsuan; Wang, Shiheng; Watanabe, Akiko; Xu, Yan
Abstract: Firms with higher R&D intensity subsequently experience higher stock returns in international stock markets, highlighting the role of intangible investments in international asset pricing. The R&D effect is stronger in countries where growth option risk is more likely priced, but is unrelated to country characteristics representing market sentiments and limits-of-arbitrage. Moreover, we find that R&D intensity is associated with higher future operating performance, return volatility, and default likelihood. Our evidence suggests that the cross sectional relation between R&D intensity and stock returns is more likely attributable to risk premium than to mispricing.